MICROCONTROLLER IMPLEMENTATION FOR BATTERY MANAGEMENT SYSTEM ON PORTABLE POWER SUPPLY WITH AUTOMATIC AND MANUAL BATTERY SWITCHER (POSAMBAS) - Irfaan Sya'baani, Muhammad
Portable power supply with automatic and manual battery switcher (posambas) is a device used to supply automatic traffic counting systems (ATCS). Posambas consists of a user interface (UI) system, a microcontroller and a battery management system. The UI system is in charge of displaying data to the user via cellphone, the microcontroller is the brain of the battery management system and the battery management system is in charge of controlling the battery. The making of posambas uses the interview method of prospective tool users, taking data such as currents and temperatures, and literature studies that support problem solving in software and testing the software. This section discusses the microcontroller which consists of a data processing system and a communication system. The data processing system functions to process data obtained from the battery management system which will then be further processed or sent to the cellphone. The communication system between the cellphone and the microcontroller uses direct communication (Wi-Fi), the microcontroller functions as a router using the type of text / html message. The microcontroller provides several web pages with a specific Uniform Resource Locator (URL) which will be accessed by the UI system before being displayed to the user. The program used is Arduino 1.8.13, the hardware used are NodeMCU ESP8266 v3 hardware, ACS712 current sensor and DHT11 temperature sensor. The results of the posambas test showed that the tool was able to send messages without error in less than one second at a radius of less than 5m from the device, was able to read pins connected to the battery, was able to carry out an automatic switching process for existing cases, and in testing was able to supply tools more than 3.5 hours. So, posambas is able to supply tools without shutting down during the switching process and is able to send messages to the UI system without any errors.